Effect of Staphylococcus aureus in experimental pneumonia mouse model on promotion of mBD-3 expression through activation of the ERK1/2 pathway - Ni, Yongqing; Bi, Xiaoduo; Zhao, Pengwei (Vojnosanitetski pregled, 2023)
Background/Aim. Staphylococcus aureus (S. aureus) is a gram-positive pathogen that causes various human diseases. S. aureus causes pneumonia, which is characterized by localized tissue necrosis. The aim of the study was to explore the expression of mouse β-defensin 3 (mBD-3) induced by S. aureus in mouse lungs and the effect of mBD-3 expression on the mitogen-activated protein kinase (MAPK) pathway. Methods. An experimental model of S. aureus pneumonia in mice was developed, and the expression of mBD-3 and activation of the MAPK pathway were investigated using the methods of immunofluorescence and western blot. Results. The experimental model was created successfully. The number of white blood cells was elevated 48 and 72 hrs after the introduction of bacteria through mouse airways, and bronchiolar mucosal hyperemia was observed, along with a large number of white blood cells and mucus in the bronchioles. The mBD-3 expression levels 48 and 72 hrs after the induction of infection were greater than the levels in the control group and 24 hrs after the induction. The amount of phosphorylated extracellular signal-regulated kinase (ERK1/2) was increased 48 and 72 hrs after infection induction, compared with the levels in the control group and 24 hrs after induction. The expression of mBD-3 was lower when ERK1/2 phosphorylation was inhibited by the U0126 inhibitor. Conclusion. S. aureus in experimental pneumonia mouse model accelerates mBD-3 expression in the mouse lung mainly through an ERK1/2-dependent signaling pathway.
Keywords: defensins; disease models, animal; pneumonia, staphylococcal; signal transduction; staphylococcus aureus